Health‐related quality of life in active surveillance and radical prostatectomy for low‐risk prostate cancer: a prospective observational study (HAROW ‐ Hormonal therapy, Active Surveillance, Radiation, Operation, Watchful Waiting). (20th April 2018) - Ansmann, Lena; Winter, Nicola; Ernstmann, Nicole; Heidenreich, Axel; Weissbach, Lothar; Herden, Jan
Abstract : Objectives: To compare health‐related quality of life (HRQOL) between patients with localised prostate cancer in an active surveillance (AS) group and a radical prostatectomy (RP) group, as evidence shows that both groups have similar oncological outcomes. Thus, comparative findings on the patients' HRQOL are becoming even more important to allow for informed treatment decision‐making. Patients and Methods: The Hormonal therapy, Active Surveillance, Radiation, Operation, Watchful Waiting (HAROW) study is a prospective, observational study designed to collect data for different treatment options for newly diagnosed patients with localised prostate cancer under real‐life conditions. At 6‐month intervals, clinical data (D'Amico risk categories, Charlson Comorbidity Index) and HRQOL (European Organisation for Research and Treatment of Cancer quality of life questionnaire 30‐item core questionnaire) were collected. Data were analysed by longitudinal multilevel analysis for patients with localised prostate cancer under AS and RP. Results: Data from 961 patients (556 RP, 405 AS) were considered. The follow‐up was 3.5 years (median 2 years). The results reveal significant, but not clinically relevant advantages for patients with low‐risk prostate cancer managed with AS in contrast to RP concerning global HRQOL as well as role, emotional and social functioning over time, after controlling for age, comorbidities, and partnership status. In some, but not all HRQOL scales, RP patients start with a slightly lower HRQOL and recover up to the level of AS patients within 1–2 years after diagnosis. Conclusion: HRQOL is an important aspect in the decision‐making and advising process for patients with prostate cancer. In many aspects of HRQOL, AS is associated with more favourable outcomes than RP within the first 1–2 years after diagnosis in our observational design, although the differences were not clinically significant. The result that HRQOL in AS patients is at least as high as in RP patients should be considered when advising patients about the different treatment options for low‐risk localised prostate cancer.